TaqIB polymorphism in the cholesteryl ester transfer protein (CETP) gene influences lipid responses to the consumption of kiwifruit in hypercholesterolaemic men. Issue 6 (1st November 2013) - Gammon, Cheryl S.; Minihane, Anne M.; Kruger, Rozanne; Conlon, Cathryn A.; von Hurst, Pamela R.; Jones, Beatrix; Stonehouse, Welma
Abstract : Fruit and vegetables are key elements of a cardioprotective diet, but benefits on plasma lipids, especially HDL-cholesterol (HDL-C), are inconsistent both within and between studies. In the present study, we investigated whether four selected HDL-C-related polymorphisms (cholesteryl ester transfer protein ( CETP ) Taq1B, APOA1 − 75G/A, hepatic lipase ( LIPC ) − 514C → T, and endothelial lipase ( LIPG ) I24582) modulate the plasma lipid response to a kiwifruit intervention. This is a retrospective analysis of data collected during a 12-week randomised controlled cross-over trial. A total of eighty-five hypercholesterolaemic men completed a 4-week healthy diet run-in period before being randomised to one of two 4-week intervention sequences of two green kiwifruit/d plus healthy diet (kiwifruit intervention) or healthy diet alone (control intervention). The measurement of anthropometric parameters and collection of fasting blood samples were carried out at baseline 1 and after the run-in (baseline 2) and intervention periods. At baseline 2, B1/B1 homozygotes of the CETP Taq1B gene had significantly higher total cholesterol:HDL-C, TAG:HDL-C, and apoB:apoA1 ratios and small-dense LDL concentrations than B2 carriers. A significant CETP Taq1B genotype × intervention interaction was observed for the TAG:HDL-C ratio ( P = 0·03). B1/B1 homozygotes had a significantly lower TAG:HDL-C ( − 0·23 (sd 0·58) mmol/l; P = 0·03) ratio after the kiwifruit intervention than after the control intervention, whereas the ratio of B2 carriers was not affected. The lipid response was not affected by other gene polymorphisms. In conclusion, the significant decrease in the TAG:HDL-C ratio in B1/B1 homozygotes suggests that regular inclusion of green kiwifruit as part of a healthy diet may improve the lipid profiles of hypercholesterolaemic men with this genotype.